O cuidado às pessoas com estomia intestinal de eliminação e a seus familiares na perspectiva de profissionais da enfermagem - Dalmolin, Angélica (2019)
The making of an omentum is an impactful surgical procedure, responsible for altering the biological, physical and psychological system of the patient, impacting on the quality of life of these people. The family of the person with estomies also experiences repercussions, because it is an episode that involves family context, characterizing itself as a collective experience. Nursing care for the person with the stoma and his / her family is a challenge, requiring scientific and practical knowledge that can meet the different dimensions of care. The lack of knowledge about how to care for and manage the stoma during the perioperative period underscores the need for a theoretical-scientific deepening about the complexity of care for this population. In view of the above, it aims to understand how care occurs to people with intestinal elimination stomies and their relatives from the perspective of nursing professionals. The specific objectives are: to identify the knowledge of nursing professionals regarding the care of people with intestinal elimination and their families; describe the care actions of nursing professionals to people with intestinal elimination and their families; to know the potential and / or difficulties experienced by nursing professionals regarding the care of people with intestinal elimination and their families. This is a qualitative research, of a descriptive nature, performed in the context of the Clinical Surgical Unit of a University Hospital. The participants were 21 professionals of the nursing team, being the data obtained from the techniques of non-participant observation, documentary analysis and semi-structured interview, from March to June 2018. Data were analyzed according to the spiral analysis technique data, proposed by Creswell (2014), which consists of four steps: data organization, reading and reminders, description, classification and interpretation of data in codes and themes, and representation and visualization of data. The ethical aspects of CONEP / CNS Resolution 466/2012 were respected, and the research protocol was approved under nº 81422217.0.0000.5346. The analysis of the data culminated in the organization of four themes and 12 units, which address: the person with the stoma and care from the perspective of the nursing professionals; knowledge and practices of nursing professionals in care; educational guidelines and apperception of the professionals about the family. he professionals reveal their perceptions about the person with the stoma, care and family participation in the caring process, crossing the intervening factors that comprise nursing work practice. Thus, it was possible to perceive that care for people with stomies and their families is fragmented, with the physical and physiological demands of management and care of the stoming and the collecting equipment being directed, not contemplating the biopsychosocial dimensions that comprise the process of health-illness experienced by the person with the stomach. Knowing the essence of care for people with stomies can result in reflections about nursing care, enabling them to think strategies to overcome the perceived fragilities and contribute to the planning and implementation of effective actions of continuity of care.